2020
DOI: 10.1021/acscatal.9b04429
|View full text |Cite
|
Sign up to set email alerts
|

Descriptor Design in the Computational Screening of Ni-Based Catalysts with Balanced Activity and Stability for Dry Reforming of Methane Reaction

Abstract: Dry reforming of methane (DRM) is an important reaction in the actual environmental and energy crisis context. It enables the production of syngas from CO 2 and CH 4 reforming. While Ni catalyst presents a high activity regarding this process, it often suffers from deactivation. It was found that the Sn-doped Ni catalyst can avoid carbon deposition, but a decrease in DRM reactivity was also observed. In this work, we used density functional theory calculations in combination with microkinetic modeling first to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 77 publications
0
62
0
Order By: Relevance
“…Ni‐Pd/Al 2 O 3 has lower activity than that of Ni/Al 2 O 3 despite the lowest activation energy barrier for feed gas conversion. According to Chen and coworkers, if the energy barrier for CH 4 decomposition is less than that for CO 2 dissociation, the catalytic resistance to carbon coking would decrease 56 . In DRM, the formation of C* on the catalyst surface originates from CH 4 decomposition, and oxygen species that oxidize adsorbed carbon comes from CO 2 dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…Ni‐Pd/Al 2 O 3 has lower activity than that of Ni/Al 2 O 3 despite the lowest activation energy barrier for feed gas conversion. According to Chen and coworkers, if the energy barrier for CH 4 decomposition is less than that for CO 2 dissociation, the catalytic resistance to carbon coking would decrease 56 . In DRM, the formation of C* on the catalyst surface originates from CH 4 decomposition, and oxygen species that oxidize adsorbed carbon comes from CO 2 dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…The catalysis microkinetic analysis package (CatMAP), [42][43][44] which is a powerful and flexible powerful package, was researched by Nørskov's group to study the microkinetic modeling by utilizing descriptor-based analysis. CatMAP as a formidable tool has been used extensively to study the trends across various catalysts.…”
Section: Microkinetic Model Simulationmentioning
confidence: 99%
“…found that combining DFT with microkinetic modelling approach, the Sn‐doped Ni catalysts surface with weak adsorption strength of carbon increased the resistance of coke deposition compared with the pristine Ni. However, the lower affinity of carbon caused an improvement in the dissociation barrier of CH 4 and CO 2 , the DRM activity was decreased at the same time [19] . Additionally, the reducibility and basicity properties of Sn species also have significant influences on the catalytic performance [16] …”
Section: Introductionmentioning
confidence: 99%